PHARMACOVIGILANCE INSIGHTS: A RARE COHORT STUDY ON HYPERSENSITIVITY REACTIONS TO INTRAVENOUS IRON SUCROSE IN POSTPARTUM ANEMIC WOMEN AT TERTIARY CARE HOSPITAL, TAMILNADU - KRISHNA RAVI; SENTHILKUMAR PALANIAPPAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aims to investigate the incidence, severity, and timeline of hypersensitivity reactions (HSRs) associated with intravenous (IV) iron sucrose and to evaluate the effectiveness of management strategies in postpartum anemic (PPA) women using a structured pharmacovigilance approach. Methods: The 2-year, single-center, prospective observational cohort study was conducted in obstetrics and gynecology at a tertiary care hospital in Tamil Nadu. Among 238 PPA women, 129 received a standard dose of iron sucrose and were categorized into adverse drug reaction (ADR, n=11) and non-ADR (n=118) groups. To identify potential risk factors for HSRs, we performed a nested case–control analysis, comparing the 11 cases who experienced HSRs with the 118 controls from the same cohort who did not. A Delphi panel assessed ADRs and graded HSRs using the World Health Organization-Uppsala Monitoring Centre causality scale and Ring–Messmer classification, respectively. The data were analyzed using Fisher’s exact test. Results: The HSR incidence was 8.5%. Most of the patients experienced Grade 2 HSR (63.64%) moderate ADR, followed by Grade 3, severe, potentially life-threatening (27.27%), requiring emergency management, with no fatalities. Demographics showed no significant association with ADRs (p>0.05). Patients with severe anemia appeared to increase the likelihood of ADRs (odds ratio = 2.77; 95% confidence interval: 0.573–13.42; p=0.204, though statistically non-significant. Over half of HSRs (54.5%) occurred after multiple doses, and 72.7% developed within 15 min of infusion. One medication error caused recurring reactions. Most ADRs (91%) were classified as probable/likely. Conclusion: This study highlights the critical need for active pharmacovigilance in tracking, managing rare and unpredictable ADRs of IV iron sucrose, necessitating pre- and post‐infusion risk assessments, immediate intervention, and infusion policy optimization in the future.